2018
DOI: 10.1111/ijal.12208
|View full text |Cite
|
Sign up to set email alerts
|

CLIL and pedagogical innovation: Fact or fiction?

Abstract: This article presents the outcomes of a large‐scale program evaluation into whether the pedagogical innovation which is associated theoretically to CLIL is actually trickling down to on‐the‐ground practice. To this end, three sets of questionnaires have been applied and semi‐structured interviews have been conducted with 2,633 teachers, students, and parents in three monolingual communities in Spain in order to carry out an in‐depth analysis of where we stand in the process of implementing CLIL methodology, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 22 publications
1
39
0
4
Order By: Relevance
“…The DST educational technology establishes a meaningful and inclusive multimodal learning context (Angay-Crowder et al 2013;Madrid and Cañado 2018;Cañado 2018;Rubino et al 2018) that facilitates a community of practice formation (Lave and Wenger 1991;Wegner and Nückles 2015). Since EFL students might have different life experiences and sociocultural backgrounds as well as different proficiencies in the target language, DST becomes a middle ground (Aikenhead 1996;Nakata 2018;Ruddell et al 2016) for the EFL students' negotiation of the concepts being studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DST educational technology establishes a meaningful and inclusive multimodal learning context (Angay-Crowder et al 2013;Madrid and Cañado 2018;Cañado 2018;Rubino et al 2018) that facilitates a community of practice formation (Lave and Wenger 1991;Wegner and Nückles 2015). Since EFL students might have different life experiences and sociocultural backgrounds as well as different proficiencies in the target language, DST becomes a middle ground (Aikenhead 1996;Nakata 2018;Ruddell et al 2016) for the EFL students' negotiation of the concepts being studied.…”
Section: Discussionmentioning
confidence: 99%
“…In general, CLIL research has reported positive outcomes (Somers 2017). However, a recent large-scale CLIL program evaluation in Spain revealed a lack of key egalitarianism or social inclusion principals essential to CLIL education (Cañado 2018). CLIL materials and teaching resources were also criticised for their lack of authenticity and scarce integration of technology (Cañado 2018), highlighting the importance of inclusiveness and authenticity in teaching content knowledge to EFL students (Cañado 2018;Darío 2014).…”
Section: Bridging Literacy and Science Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…CLIL pedagogy has many overlaps with what other language instruction approaches propose (see [ 15 , 74 , 75 ]). For example, CLIL is student-centred, which is similar to task-based, project-oriented, and cooperative learning methods.…”
Section: Previous Studies Reviewedmentioning
confidence: 99%
“…Another observation regarding CLIL research is that some of the initial enthusiasm concerning CLIL and its benefits, as put forward by numerous studies, has recently been questioned (Pérez Cañado, 2018). Previously, it was often assumed that teaching in a foreign language would provide a "language bath" that would naturally benefit the learning process (Dalton-Puffer, 2007, p. 3).…”
mentioning
confidence: 99%